Speed and persistence of risk in pandemic and the roadmap for return - Villacorta Cavero, Armando Manuel (2020)
Objective: Make a theoretical-practical review of the speed and persistence of pandemic risk and the return roadmap. Method: Non-experimental and descriptive study. Management articles and models published in indexed scientific journals and regulatory institutions were analyzed; as well as articles published by worldwide leading consulting firms. Results: It was observed that the risk management has been studying and incorporating new variables, such as speed and persistence (related with time). Conclusions: Concerning to the theoretical part it concluded that including in the analysis of risk management, the variables of speed and persistence, becomes highly important in a COVID-19 environment. In the practical part, a proposal for actions is presented in order to organizations return to their operations in the midst of this pandemic.